THE MAIN TRAINING METHODS USED IN SPEED SKATING AND THEIR INFLUENCE OVER SPORT PERFORMANCES (GYMNASIUM, 2009)
The development of speed skating has met lately a spectacular evolution also in the countries thathave a relatively new tradition in this sport, countries that, of many times, have borrowed methods andmeans from countries with an older tradition in speed skating, adapting to the bio-psycho-somaticcharacteristics specific to the zones but also, and not in the last place, to the existent base in these countries.This paper points out some of the main training methods used by great champions, methodsdeveloped by foreign and Romanian scientific investigators.